Integration of Community-Based Sustainable Waste Management in Circular Economy Policy: A Study in West Aceh Regency - Sri Wahyu Handayani; Zuhrizal Fadhly (Journal of Political and Governance Studies, 2025)
Background: Waste management has become one of the most pressing environmental challenges in West Aceh Regency, where population growth and consumption patterns continue to increase waste generation. Integrating community-based sustainable waste management into circular economy policies represents a strategic approach to balance environmental protection, economic growth, and social well-being. The Triple Bottom Line (TBL) framework—focusing on the interconnection between profit, people, and planet—offers a comprehensive lens to evaluate sustainability outcomes at the local level. This study aims to analyze how community-based waste management initiatives contribute to the implementation of circular economy principles in West Aceh Regency. Methods: The research adopts a qualitative approach with an in-depth case study design. Data were collected through field observations, semi-structured interviews, and document analysis. Thematic analysis was employed to identify key patterns, enabling factors, and challenges in the integration process between community initiatives and local circular economy policies. Results: The findings indicate that community participation—manifested through waste banks, organic waste processing, and recycling-based microenterprises—has generated multiple benefits, including additional household income, increased environmental awareness, and a reduction in domestic waste volume by up to 30% per month. Despite these achievements, several constraints persist, particularly in terms of infrastructure limitations, weak law enforcement, and inconsistent public engagement. Conclusions: Strengthening sustainable waste management in West Aceh requires a more holistic policy framework that empowers communities through continuous education, institutional support, and multi-stakeholder collaboration. Integrating the TBL approach into local governance not only enhances environmental and social outcomes but also advances the realization of the Sustainable Development Goals (SDGs) at the regional level.